FOTOCATÁLISE HETEROGÊNEA E ULTRAFILTRAÇÃO COMO PÓSTRATAMENTO DE EFLUENTES DE INDÚSTRIAS DE PAPEL E CELULOSE - RANSOLIN, VANESSA MARIA RIBAS (2017)
The main objective of this research was to evaluate the processes of heterogeneous photocatalysis and ultrafiltration in the treatment of effluents from pulp and paper industries. For this purpose, it was first optimized the experimental conditions for the ultrafiltration system, as well as for the photocatalytic process. The results indicated that the best operating condition for ultrafiltration is with the Reynolds number 1653, corresponding to a flow of 96 L h-1 and a pressure of 1,5 bar. For photocatalysis, pH 3 and TiO2 concentration of 0.5 g L-1 were found to be ideal for the process. Then, the removal of the physical-chemical parameters COD, color, turbidity, total phenols, total suspended solids and total solids were evaluated. With the ultrafiltration, it was possible to remove 97,3 % of the effluent turbidity, however, for the other parameters evaluated, the removal was moderate, reaching a maximum of 57,3 % COD removal, 35,8 % color, 42,5 % phenolic compounds, 57,7 % TSS and 6,4 % TS. The photocatalytic process was very efficient in removing the evaluated parameters, reaching 97,9 % of COD removal, 97,2 % of color, 65,5 % of turbidity and 89,6 % of phenolic compounds. However, the removal of solids was low, with 23,6 % of TSS removal and 1,1 % of TS. It was also verified the reduction of the spectral area of the effluent and it was observed that with ultrafiltration there was only 5,9 % of reduction after 120 minutes of filtration, but with the photocatalysis there was 98,2 % reduction after 90 minutes of reaction. The combined application of the ultrafiltration and heterogeneous photocatalysis processes was also evaluated, however, based on the results obtained, it was concluded that the use of the combined processes is not justified, since statistically there was no improvement in the percentage of removal of the parameters evaluated when compared to the systems applied alone.